2019
DOI: 10.1186/s12955-019-1227-5
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the effects of internet usage on the happiness of Japanese university students

Abstract: Background Besides research on psychiatric diseases related to problematic Internet use (PIU), a growing number of studies focus on the impact of Internet on subjective well-being (SWB). However, in previous studies on the relationship between PIU and SWB, there is little data for Japanese people specifically, and there is a lack of consideration for differences in perception of happiness due to cultural differences. Therefore, we aimed to clarify how happiness is interdependent on PIU measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 34 publications
4
17
1
1
Order By: Relevance
“…The high mean total exposure score implies that university students have high exposure to both mass media and social media during the COVID-19 outbreak. This finding replicates evidence from previous research, indicating high use of online media (particularly social media) by the younger generation and specifically university students [ 21 - 24 ]. In this study, we also found that university students were exposed to equal amounts of COVID-19–related information from both mass and social media.…”
Section: Discussionsupporting
confidence: 90%
“…The high mean total exposure score implies that university students have high exposure to both mass media and social media during the COVID-19 outbreak. This finding replicates evidence from previous research, indicating high use of online media (particularly social media) by the younger generation and specifically university students [ 21 - 24 ]. In this study, we also found that university students were exposed to equal amounts of COVID-19–related information from both mass and social media.…”
Section: Discussionsupporting
confidence: 90%
“…A meta-analysis of 23 studies across different age groups found a negative correlation between problematic internet use and well-being [32]. A study of Japanese university students also found a similar result [33]. Although internet and social media can increase social interaction with friends and family, Kraut et al found that this phenomenon is only true for people who were already rich in social capital, and for those who lack interpersonal connections in real life, internet use tends to reinforce social isolation [34].…”
Section: Plos Onementioning
confidence: 79%
“…De Vries et al found that internet users with psychiatric disorders are more likely to experience sleep problems, depression, anxiety, and autism (20). Several studies have considered the quality of sleep in people with IA (12,18,(44)(45)(46), but in some studies no significant relationship has been found (19). In studies that have reported a significant relationship between IA and sleep disturbances, the severity of such a relationship has been varied.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Hence, the consistency across the studies strengthens our findings, emphasizing the association between IA and sleep. The consistency could be attributed to the commonly used IA and sleep instruments: 17 studies used the IAT to assess IA (19,20,43,45,47,52,53,56,(58)(59)(60)(61)(62)(63)(64)(65)68) and nine used the PSQI to assess sleep problems (38, 45-47, 57, 60, 62, 63, 66). Furthermore, the high quality of these studies (all studies have clearly defined their objectives, variables, and measurement using well-established criteria) and the comparable participants in these studies (19 studies on high school or university students [19, 38, 43-47, 52, 53, 57, 58, 60-62, 64-68]) ensure the homogeneity among the studies and result in consistent findings.…”
Section: Accepted Manuscriptmentioning
confidence: 99%